STRATEGI PENGEMBANGAN INDUSTRI KREATIF BERBASIS SUMBERDAYA PESISIR DAN LAUT DI KOTA AMBON - Renoldy Lamberthy Papilaya; Johanis Hiariey; Tesalonika Risakotta (Universitas Pattimura, 2018)
Coastal resources are generally used by people into a crafts include fish scales, pearls shells, coconuts, shellfish, snails, coastal pandanus, bintangur and variety of coastal vegetation. To find out how the business continuity community needs to be studied Strength, Weakness, Opportunities and Threats (SWOT) of the business. Respondents were used in the study 0f 20 sample out of a population of 56 people (35,7%) consists of buyers, sellers and institutional industries and tourism. This study analyzed the respondents assessment of the results of Internal Factors Analysis Summary (IFAS) and External Factors Analysis Summary (EFAS). The assessment results are then calculated an overall Ratio of Consistency (CR), if CR â‰¤ 0,1, the respondents have consistency in answering the questionnaire given. IFAS into strengths like quality of the product is according to counsumer tastes, ease of access to raw materials, skilled labor and experienced. While internal strategic factors of weakness such as: lack of media promotion, lack of financial bookkeeping. EFAS into opportunities such as private consumption will rise crafts, the market share is still widespread. While the factors external strategy that pose a threat to easy to imitate, regeneration of hard labor. Consistency Ratio (CR) of 0,07 indicates a decision taken by the respondent to determine priorities fairly consistent, meaning that priorities can be implemented are: improving the quality of product and market development as well as the flexibility of the product in order to follow changes in behavior and market demand.